2018
DOI: 10.1089/ars.2017.7248
|View full text |Cite
|
Sign up to set email alerts
|

Activating the Chromatin by Noncoding RNAs

Abstract: The ncRNA field is coming out of its infancy and we are gaining a global picture of the importance of ncRNAs. However, detailed mechanisms of action of the different ncRNAs are still to be determined. This may reveal novel ways of transcriptional regulation, which will facilitate our ability to utilize these regulatory pathways for research and therapeutic purposes. Antioxid. Redox Signal. 29, 813-831.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 169 publications
0
11
0
Order By: Relevance
“…For example, small RNA-mediated transcriptional gene activation (TGA) has been reported in some cases, whereby synthetic small RNAs or endogenous miRNAs targeted to gene promoters can induce increases in gene expression 6,7 . TGA involves an epigenetic mechanism, although a detailed understanding of this phenomenon has thus far remained elusive 8 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, small RNA-mediated transcriptional gene activation (TGA) has been reported in some cases, whereby synthetic small RNAs or endogenous miRNAs targeted to gene promoters can induce increases in gene expression 6,7 . TGA involves an epigenetic mechanism, although a detailed understanding of this phenomenon has thus far remained elusive 8 .…”
Section: Introductionmentioning
confidence: 99%
“…145 The ncRNAs play a crucial role in gene regulation processes and epigenetic changes. 146,147 The Long intergenic non-coding RNAs (lincRNAs) have been reported to play significant roles in a number of diseases, including coronary atherosclerosis, 148 immune disease, 149 and different type of malignancies. 150 Over the years, many experimental findings have demonstrated that lincRNAs have significant roles in the pathogenesis of cardiovascular disease.…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…RNA therapeutic avenues are likely to extend in the future, as we are not limited to RNAi mechanisms in the cytoplasm but dsRNAs can also act in the nucleus to cause transcriptional gene silencing (TGS) via modification of epigenetic marks (Castel and Martienssen, 2013;Martienssen and Moazed, 2015). In addition, siRNA targeting gene promoters can also cause transcriptional activation (Laham-Karam et al, 2018), these transcription regulating small RNA can expand the repertoire of the RNA therapeutics and are likely to reach the clinics in future.…”
Section: Rna Interference-based Inhibitorsmentioning
confidence: 99%